2005
DOI: 10.1063/1.2132272
|View full text |Cite
|
Sign up to set email alerts
|

Electron and ion kinetic effects in the saturation of a driven ion acoustic wave

Abstract: The role of ion and electron kinetic effects is investigated in the context of the nonlinear saturation of a driven ion acoustic wave (IAW) and its parametric decay into subharmonics. The simulations are carried out with a full–particle-in-cell (PIC) code, in which both ions and electrons are treated kinetically. The full-PIC results are compared with those obtained from a hybrid-PIC code (kinetic ions and Boltzmann electrons). It is found that the largest differences between the two kinds of simulations take … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 34 publications
(50 reference statements)
1
4
1
Order By: Relevance
“…Our collisionless and noiseless (to machine precision) Vlasov simulations are 2D+2V (two configuration space + two velocity space dimensions). The results obtained reveal a picture of IAW decay that is qualitatively different from previous 2D numerical [9][10][11][12][13] and theoretical [12][13][14] treatments where the electrons were not treated as kinetic, reveal decay processes not captured by fully kinetic 1D simulations [15][16][17][18], and allow measurement of linear growth rates not possible in previous fully kinetic 2D/3D simulations [19] due to discrete particle noise.…”
contrasting
confidence: 79%
“…Our collisionless and noiseless (to machine precision) Vlasov simulations are 2D+2V (two configuration space + two velocity space dimensions). The results obtained reveal a picture of IAW decay that is qualitatively different from previous 2D numerical [9][10][11][12][13] and theoretical [12][13][14] treatments where the electrons were not treated as kinetic, reveal decay processes not captured by fully kinetic 1D simulations [15][16][17][18], and allow measurement of linear growth rates not possible in previous fully kinetic 2D/3D simulations [19] due to discrete particle noise.…”
contrasting
confidence: 79%
“…Figure 8 shows the comparison of the full-Vlasov simulation (red dots) and the hybrid-Vlasov (blue dots) simulation. It is found that electron kinetic effects will promote the TID process, which is in agreement with earlier results reported in [73,74].…”
Section: Merge Mechanism-growth Of Subharmonics Induced By Tid Instab...supporting
confidence: 92%
“…Both reflectivity images show a drop in reflectivity near the end of the simulation. In both cases a decay of the SBS driven IAW in fractional harmonics of the primary wave [20,24,[71][72][73][74][75][76][77][78][79] takes place and induces SBS saturation. However, the decay modes are not the same for the two cases.…”
Section: Low K Epw λ D -Regimementioning
confidence: 99%
“…One can also observe that the slope of the ω-k diagram is less steep the long plasma case, consistent with an increased value of the ion-acoustic velocity due to electron heating. SBS saturation is also partially related to ion and electron kinetic effects and their interplay with the IAW decay into fractional harmonics [74,75] , and discussed in more detail in recent studies including 1D and 2D simulations [24,[78][79][80] . In fact, there is no fundamental difference between the two cases when analysing the ion phase space.…”
Section: Low K Epw λ D -Regimementioning
confidence: 99%